2020
DOI: 10.1021/acsomega.0c03353
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum Oxide Nanoparticle Films Deposited from a Nonthermal Plasma: Synthesis, Characterization, and Crystallization

Abstract: Aluminum oxide, both in amorphous and crystalline forms, is a widely used inorganic ceramic material because of its chemical and structural properties. In this work, we synthesized amorphous aluminum oxide nanoparticles using a capacitively coupled nonthermal plasma utilizing trimethylaluminum and oxygen as precursors and studied their crystallization and phase transformation behavior through postsynthetic annealing. The use of two reactor geometries resulted in amorphous aluminum oxide nanoparticles with simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 72 publications
3
25
0
Order By: Relevance
“…Moreover, more attention has been focused on the perspective of copper oxide in various aspects such as antibacterial agents [12], catalysis [13], food packaging [14], sensors [15] and medicine [16]. Recently, there has been a growing awareness of the development of aluminium oxide nanoparticles (Al 2 O 3 NPs) which have a high specific surface area with extraordinary optical, catalytic, thermodynamic stability properties for progressive engineering and industrial applications [17][18][19]. Few studies reported the use of CuO/Al 2 O 3 in sensing applications such as Khan et al [20] studied the electrochemical oxidation of ammonia over copper oxide impregnated γ-Al 2 O 3 nanocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, more attention has been focused on the perspective of copper oxide in various aspects such as antibacterial agents [12], catalysis [13], food packaging [14], sensors [15] and medicine [16]. Recently, there has been a growing awareness of the development of aluminium oxide nanoparticles (Al 2 O 3 NPs) which have a high specific surface area with extraordinary optical, catalytic, thermodynamic stability properties for progressive engineering and industrial applications [17][18][19]. Few studies reported the use of CuO/Al 2 O 3 in sensing applications such as Khan et al [20] studied the electrochemical oxidation of ammonia over copper oxide impregnated γ-Al 2 O 3 nanocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…7C1). The peaks marked with a star (*) in 43,56,57 The effect of annealing at 1100 1C for 4 h on the bimetallic Al 2 O 3 -Fe 2 O 3 nanoparticles was also characterized using TEM (Fig. S5, ESI †).…”
Section: Resultsmentioning
confidence: 99%
“…These phase transitions from amorphous AlO x to α-Al 2 O 3 and α-Al 2 O 3 to α-Al 2 O 3 have been addressed previously. 43,56,57…”
Section: Resultsmentioning
confidence: 99%
“…The thickness of this layer can be increased through an anodizing process. Some alloys, such as aluminum bronze, take advantage of this property by adding aluminum to the alloy to increase its corrosion resistance [34].…”
Section: Nano-aluminamentioning
confidence: 99%